THE EFFECT OF COOKING ROLE PLAY ON FINE MOTOR DEVELOPMENT OF 3-4 YEAR-OLD CHILDREN - Anugrah Robiah Al Adawiyah; Iman NurJaman; Rd Ranie Damayanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the effect of cooking role-play on the fine motor development of 3-4-year-old children in non-formal educational institutions. The urgency of this research is based on the fact that fine motor development is a crucial aspect in supporting independence, coordination, and readiness to learn in early childhood. However, in practice, activities that stimulate fine motor skills are still minimal, as most learning is based on worksheets that lack hands-on and exploratory experiences. Therefore, engaging, interactive, and age-appropriate learning strategies are needed. The main objective of this study was to determine the condition of children's fine motor skills before and after being treated through a cooking role-play, and to analyze its effect on improving these skills. This research is expected to provide an empirical overview of the effectiveness of this method as an innovative approach to improving fine motor skills. The targeted results of this study include: first, revealing the initial conditions and increasing fine motor skills of children after participating in the activity; second, finding a significant influence of cooking role play on improving fine motor skills of early childhood; and third, practical recommendations in the development of innovative game-based learning that can be utilized by educators and PAUD institutions to improve the quality of motor stimulation in early childhood. Thus, this study is expected to be a reference in enriching fun and educational learning methods, as well as supporting the optimization of motor development in children aged 3-4 years.